2012
DOI: 10.1075/ni.22.1.08van
|View full text |Cite
|
Sign up to set email alerts
|

Maneuvering between the individual and the social dimensions of narratives in a poor man’s discursive negotiation of stigma

Abstract: In current Western consumer societies, the poor are excluded and occupy stigmatized positions. By analyzing an interview with a poor man, I look at how stigma is discursively negotiated through the interplay between individual and social dimensions of narratives. First, the interviewee resists the interviewer's 'poor man'-category projection by setting up alternative groups. Second, he invokes and aligns with dominant discourses regarding the necessity to own consumer goods and find a work-life balance, by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Finally, as Van De Mieroop (2012 has shown, narrative analysis offers an innovative and promising avenue for investigating important issues relating to financial hardship. With an increase of personal debt in the UK (National Debtline, 2019), that may well be exacerbated in the coming years by the ongoing Coronavirus pandemic, there is an increasing need to both understand and evaluate how organisations recover money, both locally and globally.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as Van De Mieroop (2012 has shown, narrative analysis offers an innovative and promising avenue for investigating important issues relating to financial hardship. With an increase of personal debt in the UK (National Debtline, 2019), that may well be exacerbated in the coming years by the ongoing Coronavirus pandemic, there is an increasing need to both understand and evaluate how organisations recover money, both locally and globally.…”
Section: Discussionmentioning
confidence: 99%
“…The study acknowledges the voices of individuals with comorbid DUD and ASPD and provides insight into how they experience and narrate about treatment and change (Collins & Nicholson, 2002). Both study cases had accepted participation in a treatment program targeting their ASPD, and were willing to share aspects of their behavior and lifestyle which to others with the same diagnosis could be regarded as an unwelcome attempt to engage in self-stigmatization (Van De Mieroop, 2012). To reduce bias, the two first authors who designed and conducted the study did not conduct the interviews.…”
Section: Limitationsmentioning
confidence: 99%
“…As such, the narrator avoids the attribution of group features, and this may function as a way to negotiate the membership of a stigmatized group identity, for example. For instance, in a previous study (Van De Mieroop 2012a) in which I analyzed an interview with an poor, unemployed Belgian man, the interviewee described his busy "career" while referring to his work as a volunteer. He thus precludes any imputation of laziness from his listener -a feature that sociological research has demonstrated to be an important Belgian poverty stereotype ("poor people are lazy").…”
Section: Collective Identities In Narrativesmentioning
confidence: 99%